Article Commentary: Considerations in Civil Commitment of Individuals with Substance Use Disorders. Issue 1 (January 2016) - Cavaiola, Alan A.; Dolan, David
Several states currently have enacted laws that allow for civil commitment for individuals diagnosed with severe substance use disorders. Civil commitment or involuntary commitment refers to the legal process by which individuals with mental illness are court-ordered into inpatient and/or outpatient treatment programs. Although initially civil commitment laws were intended for individuals with severe mental illness, these statutes have been extended to cover individuals with severe substance use disorders. Much of the recent legislation allowing for civil commitment of individuals with substance use disorders has come about in response to the heroin epidemic and is designed to provide an alternative to the unrelenting progression of opioid use disorders. Civil commitment also provides an opportunity for individuals with opioid use disorders to make informed decisions regarding ongoing or continued treatment. However, civil commitment also raises concerns regarding the potential violation of 14th Amendment rights, specifically pertaining to abuses of deprivation of liberty or freedom, which are guaranteed under the 14th Amendment to the United States Constitution. This commentary examines these issues while supporting the need for effective brief civil commitment legislation in all states.